STRATEGI PENGEMBANGAN USAHA SIRUP KALAMANSI MELALUI PROGRAM ONE VILLAGE ONE PRODUCT (OVOP) DI KOTA BENGKULU - Mardiati Sari, Dian; Sureta, Nurdina (STIA Bengkulu, 2024)
The purpose of this research is to find out the strategy to improve economic value of Kalamansi syrup in the Bengkulu City. This research is descriptive research . Data analysis method used is descriptive analysis and SWOT analysis. Based on the results of the analysis of the data obtained results that the strategy improvement of Kalamansi syrup in the Bengkulu City : (a) support development of more modern processing technology; (b) Conducting orange of kalamansi to take care of the continuity of production; (c) Cooperation between worker in pricing product; (d) Program reinforcement and development micro and small industries; (e) Support capital employed of financial institution; (f) Improve product promotion intensity on local media and national; and (g) Network marketing.